Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/1467-8489.12390
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Sustainable Agricultural Practices and Rural Incomes: Evidence from China

Abstract: Relatively little is known about the association between Internet use and environmentally-friendly agricultural innovation adoption. To fill this void, this study examines the impact of Internet use on the adoption of sustainable agricultural practices (SAPs) and their heterogeneous effects on farm income and household income. Unlike previous studies that analyse the dichotomous decision of agricultural innovation adoption, this study captures the number of SAPs adopted. We apply both endogenous-treatment Pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
97
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 66 publications
10
97
1
Order By: Relevance
“…Evidence shows that nutritional intake is determined by income [8,10,11], agricultural/food programs [12][13][14], agricultural commercialization [15], microcredit [16], farm production [17,18], nutrition labels, and communication networks [19]. Moreover, studies have found that the internet is a new factor affecting the well-being of households, especially rural households, in both developed and developing countries/regions [20][21][22][23][24][25]. Specifically, the internet may positively affect food consumption [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that nutritional intake is determined by income [8,10,11], agricultural/food programs [12][13][14], agricultural commercialization [15], microcredit [16], farm production [17,18], nutrition labels, and communication networks [19]. Moreover, studies have found that the internet is a new factor affecting the well-being of households, especially rural households, in both developed and developing countries/regions [20][21][22][23][24][25]. Specifically, the internet may positively affect food consumption [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the nutritional transition process and nutrition-related health problems in China [34][35][36], it is essential to investigate the determinants of nutritional intake. Third, since there are large differences in economic development levels and diets across China, the data used in previous studies covered relatively few areas [22][23][24][25]29].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that nutritional intake is determined by income [8,10,11], agricultural/food programs [12][13][14], agricultural commercialization [15], microcredit [16], farm production [17,18], nutrition labels and communication networks [19]. Moreover, studies have found that the internet is a new factor affecting the well-being of households, especially rural households, in both developed and developing countries/regions [20][21][22][23][24][25]. Specifically, the internet may positively affect food consumption [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nutrition transition process and nutrition-related health problems in China [34][35][36], it is essential to investigate the determinants of nutritional intake. Third, since there are large differences in economic development levels and diets across China, the data used in the previous studies covered relatively few areas [22][23][24][25]29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have found that the internet is a new factor affecting the well-being of households, especially rural households, in both developed and developing countries/regions [20][21][22][23][24][25]. Specifically, the internet may positively affect food consumption [26][27][28][29][30].…”
mentioning
confidence: 99%